Nucleotide methylation and neurocognitive phenotypes - Flitton, Miles (2018)
Epigenetic modifications are under increasing scrutiny in research of health and disease states. The most commonly researched epigenetic modification, DNA methylation, is associated with familial forms of dementia, developmental delay syndromes, and disparate cognitive phenotypes. This thesis investigates the relationship between nucleotide methylation and brain disease using three distinct approaches.